Exploring EFL Students’ Perceptions of Interlingual Subtitling as a Language Learning Task - Hidayatun, Muthiah; Hartono, Rudi; Wahyuni, Sri (Langkawi: Journal of The Association for Arabic and English, 2025)
Despite the growing body of research on audiovisual translation in language education, subtitling is often positioned merely as a supplementary learning tool rather than as a central pedagogical task. This study addresses that gap by investigating English as a Foreign Language (EFL) students’ perception of interlingual subtitling as an active translation task in a higher education context in Indonesia. Employing a qualitative descriptive case study, the research engaged 14 undergraduate students enrolled in a translation course at State Islamic Institute of Kendari. Participants created Indonesian subtitles for a TEDx Talk by Nwal Hadaki using Aegisub software. The study draws on Task-Based Language Learning (Ellis, 2003), Cognitive Load Theory (Sweller, 1998), and Walgito’s (2004) cognitive model of perception to interpret students’ experiences. Data were collected via Likert-scale questionnaires and structured digital self-reflection and analyzed using the Miles and Huberman (1994) framework. Findings demonstrate that although students perceived the task as complex and cognitively demanding, they recognized its pedagogical value in developing vocabulary, listening skills, idiomatic comprehension, and technological proficiency. Students reported increased engagement and motivation, suggesting that subtitling fosters learner autonomy and language integration. This study implies the potential of interlingual subtitling as a dynamic, skill-integrative approach in translation pedagogy within EFL contexts.